The promotion effect of uniaxial strain on hydrogen aggregation in tungsten - Ma, Fang-Fei; Li, Yu-Hao; Ren, Qing-Yuan; Zhou, Hong-Bo; Lu, Guang-Hong (Frontiers in Materials, 2023)
As the most promising candidates for plasma-facing materials, tungsten (W) will be irradiated by low-energy and high-flux hydrogen (H) isotopes plasma in future devices, leading to the severe radiation damages. Physically, these H-induced damages are intimately linked with the aggregation and super-saturated retention of H in W, while its underlying mechanism is still unclear. Here, using a first-principles method and thermodynamic models, we investigate the influence of uniaxial strain on the aggregation of interstitial H atoms in W. Despite the positive binding energy of planar H clusters, the formation of interstitial H clusters in strain-free W is very difficult due to the configurational entropy. However, the applied uniaxial strain significantly enhances the stability of H platelet, and enable the planar H clusters to form. These suggest that the uniaxial strain facilitates the nucleation and growth of planar H clusters, regardless of whether it is a compressive or tensile strain. Meanwhile, the desorption temperature of these platelet-like H clusters and their influences on vacancy formation are also calculated and discussed. Accordingly, our calculations provide a potential mechanism to account for the super-saturation of H isotopes in W-PFMs and have broad implications for the evolution of H in materials.